2021
DOI: 10.1186/s12910-021-00631-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes about end-of-life decisions, good death and principles of medical ethics among doctors in tertiary care hospitals in Sri Lanka: a cross-sectional study

Abstract: Background Competent end-of-life care is an essential component of total health care provision, but evidence suggests that it is often deficient. This study aimed to evaluate the knowledge and attitudes about key end-of-life issues and principles of good death among doctors in clinical settings. Methods A cross-sectional study was conducted among allopathic medical doctors working in in-ward clinical settings of tertiary care hospitals in Sri Lanka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Studies exploring nurses’ attitudes also found that about half of nurses find that withholding of LST is not morally the same as withdrawal [ 22 , 34 , 35 ]. Seventy percent of participants in a study conducted in tertiary care hospitals in Sri Lanka responded they found withholding LST more comfortable then withdrawing it [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring nurses’ attitudes also found that about half of nurses find that withholding of LST is not morally the same as withdrawal [ 22 , 34 , 35 ]. Seventy percent of participants in a study conducted in tertiary care hospitals in Sri Lanka responded they found withholding LST more comfortable then withdrawing it [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, this study concluded that there were significant deficits in knowledge and recommended mandatory training sessions with simulations if feasible. (10) So, these aspects, which are little in daily practice for everyone, need to be improved in most medical professional populations. But knowledge of these aspects is inseparable from a respectable and effective rendition of quality health services which urges urgent measures to solve these.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sri Lanka also faces a major problem with low organ donors and a long waiting list. Cultural beliefs and customs, and lack of knowledge and legislation on Do Not Resuscitate orders, and the differences of the opinions or lack of knowledge of withdrawal/withholding of life-sustaining treatments among medical professionals contribute to low volumes of organ donation [29]. To address the ethical issues surrounding end-of-life care, a practice guideline was adopted in 2021 with the aim to safeguard the rights and dignity of the dying person and also to provide necessary support to the relatives [30].…”
Section: Challenges In Liver Transplant Programme In Sri Lankamentioning
confidence: 99%